Optimization of Academic Services Based on Quality Function Deployment: An Integration Study of Servqual Method at Graha Nusantara University - Fitri Romaito Lubis; Martua Siregar; Yusniar Harahap; Bayo Harahap; Fitrah Suci Azzahra (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2024)
This research is motivated by the need to improve academic service quality at Graha Nusantara University to meet student expectations and dynamic higher education industry demands. The study aims to analyze gaps between students' perceptions and expectations of academic services and develop innovative strategies through the integration of Quality Function Deployment (QFD) and SERVQUAL. The research employs a mixed-method approach with sequential explanatory design, conducted in 2024 involving 289 students as respondents selected through proportionate stratified random sampling from 1,038 population. Data collection utilized SERVQUAL dimension-based questionnaires and semi-structured interviews. The results identified eight service attributes with significant gaps, particularly in campus facilities (gap=-1.15), health services (gap=-1.11), and problem-solving training (gap=-1.01). Based on improvement ratio, enhancement priorities include facility cleanliness (1.59), health services (1.55), and problem-solving training (1.50). The research recommends improving cleaning systems, developing health facilities, modernizing laboratories, and implementing problem-based learning.